Effect of crude alcoholic celery (Apium graveolens) leaves extract on fertility in albino female mice (Baghdad Science Journal, 2011)
Sixty albino female mice were used in this experiment to study the possible effect of the crude alcoholic extract of the celery leaves on their fertility. These animals were randomly and equally divided into three experimental groups (20 females/group). The first and second groups were orally given a daily dose of 500 and 1000 mg/kg body weight, respectively, of the crude alcoholic extract, while the third group (control) was similarly treated, at the same time, with 0.1 ml/gm body weight of physiological saline for comparison. The treatment, however, lasted for 25 consecutive days. On day 26, after treatment was stopped, the life body weight of all animals was recorded before sacrificing the animals. Thereafter blood samples were collected by heart puncture for hormonal (estrogen, progesterone, luteinizing hormone and follicle stimulating hormone) determination. Reproductive organs (ovaries and uteri) were also isolated and preserved for histological studies. Active ingredients in the extracts were analytically tested. The test gave positive results for flavonoids, steroids, tannins and terbenoids. The effect of the extract on the studied parameters which are related to the fertility is reflected in the following results:1) significant (p